Impact of public health lecture intervention on consumption behaviour towards indigenous staple carbohydrate foods - Onodu, Bonaventure; Culas, Richard; Nwose, Ezekiel U. (International Journal Of Community Medicine And Public Health, 2020)
Background: The increase in non-communicable diseases (NCDs) experienced more in the developing countries can be attributed to changes in demography (rural to urban migration) and changes in pattern of food consumption. With the increasing incidences in diabetes globally, dietary restrictions and modifications in consumption behaviors still remains the bedrock in the prevention and management of the disease. Specific education to prevent or manage people’s lifestyle in order to combat NCDs such as diabetes are widely available, but assessment of knowledge about dietary fiber and its impact on staple foods consumption is largely unexplored. Methods: This study utilized nutritional education as an intervention strategy to bring about changes in consumers consumption behaviour, changing their perspective in consumption of root and tuber crops in relation to wheat in the study area. The intervention involved public health lecture on the nutrition values of staple carbohydrate root and tuber crop foods (cassava and yam) with focus on their dietary fibre content, relative to wheat. Results: The statistical analysis showed that there is a significant difference in the dietary habits in urban and in rural areas. Intervention resulted in shift in consumption behavior towards indigenous staple carbohydrate food crops. The changes in behavior were more obvious in urban dwellers, especially in favour of cassava consumption. Conclusions: Education or information targeted to correct the consumption behaviour of specific group of individuals stands a chance in impacting and improving their food choices and dietary behaviours.